2011
DOI: 10.1007/s10544-011-9583-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray deposition and direct patterning of polylactic acid nanofibrous microcapsules for tissue engineering

Abstract: Electrospun nanofibers composed of biodegradable polymers are attractive candidates for cell culture scaffolds in tissue engineering. Their fine-meshed structures, resembling natural extracellular matrices, effectively interact with cell surfaces and promote cell proliferation. The application of electrospinning, however, is limited to two-dimensional (2D) or single tube-like scaffolds, and the fabrication of arbitrary three-dimensional (3D) scaffolds from electrospun nanofibers is still very difficult due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 27 publications
2
19
0
1
Order By: Relevance
“…Although PLA polymer has limited solubility in ethanol, its presence in electrospun solutions did not impair the electrospinning process. These results correlate with results presented by Ikeuchi and coauthors [23] when uniform electrospun PLA microfibers from PLA in chloroform (PLA concentration 2%) solution with 20% ethanol have been produced. The morphologies of electrospun nonwoven materials from PLA polymer solutions containing AgNPs and different amounts of PEE are presented in Figure 4.…”
Section: Resultssupporting
confidence: 90%
“…Although PLA polymer has limited solubility in ethanol, its presence in electrospun solutions did not impair the electrospinning process. These results correlate with results presented by Ikeuchi and coauthors [23] when uniform electrospun PLA microfibers from PLA in chloroform (PLA concentration 2%) solution with 20% ethanol have been produced. The morphologies of electrospun nonwoven materials from PLA polymer solutions containing AgNPs and different amounts of PEE are presented in Figure 4.…”
Section: Resultssupporting
confidence: 90%
“…In another study, Xu et al (2006) showed that 1,2-dichloroethane (DCE) was a more suitable solvent for electrospraying PLA than DCM. Ikeuchi et al (2012) recently demonstrated the fabrication of PLA particles with high surface porosities due to phase separation by electrospraying 1% PLA chloroform solution containing 5% ethanol in a high humidity environment (90%).…”
Section: Compositionmentioning
confidence: 99%
“…The variation in polymer solution flow rate and humidity of electrospray environment influenced the diameter and surface porosity of the nanoparticles. The direct 3D patterning method combined with nanofibrous hollow structure of PLA particles showed improved cell interaction and biodegradability for its application in tissue regeneration [33].…”
Section: Accepted Manuscriptmentioning
confidence: 99%